Cow’s Milk Protein Allergy in an Infant - A Case Report: Life Sciences -Paediatrics - Sababathi N.T, Jana; Kharlukhi, Jacqueline; S, Sundari (International Journal of Life Science and Pharma Research, 2023)
Cow’s milk protein allergy (CMPA) is a common condition of food allergy in babies, and it is encountered in childrenwith an incidence of 2% to 7.5% estimated in the first year of life. Breast-fed and formula-fed babies can present with CMPAsymptoms, and it’s essential to diagnose CMPA to avoid the repercussion of overdiagnosis or underdiagnosis. A one-year-oldfemale child complained of fresh blood in her stools for two days which was painless. She was on breast milk and complimentaryfeeds, and her nutritional status was normal. she had been through 7 similar episodes of easy blood in stools from 4 months ofage. She was treated with IV antibiotics and initially suspected of colitis, and investigations were not done. There was no familyhistory of allergy, atopy, or asthma. On examination revealed pallor, vitals stable, and systemic examination were normal.Complete blood count shows low HB, peripheral smear shows microcytic anaemia, CRP-negative. Stool for occult bloodpositive. Faecal calprotectin was negative. USG Abdomen - normal, USG Endoscopy -Normal, Colonoscopy showedOedematous mucosa of the terminal ileum and prominent villi with erythema, sigmoid, and rectum revealed erythematous witherosion with prominent Pit pattern. Biopsy- From sigmoid and rectum showed increased eosinophils in lamina propria. Hencethe child was diagnosed to have Cow’s milk protein allergy. The mainstay treatment includes avoiding Cow’s milk consumptionfor four weeks - 6 months’ post-diagnosis. In that instance, breastfeeding mothers should be advised to avoid milk and milkproducts during breastfeeding.